A Rare Case of Ischiopagus Dicephalus Conjoined Twins with Tetrabrachius Tripus: Prenatal Diagnosis and Management: A Case Report - Ahsanudin Attamimi; Detty Siti Nurdiati; Irwan Taufiqur Rachman; Adi Ariffianto (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Objectives: This article reports a rare case of conjoined twins with ischiopagus dicephalus and tetrabrachius tripus, emphasizing the significance of early prenatal imaging and interdisciplinary therapy.Case Report: Conjoined twins are a rare congenital anomaly resulting from the incomplete division of a single fertilized ovum in monozygotic, monochorionic, monoamniotic pregnancies. Ischiopagus dicephalus is an exceptionally rare subtype characterized by two heads on a single body, with fusion of the lower thorax and pelvis. We report a 28-year-old primigravida who was diagnosed at 18 weeks’ gestation with ischiopagus dicephalus tetrabrachius tripus. Transabdominal and 3D ultrasonography revealed a unique anatomical combination: two separate heads and two independent hearts and thoracic cavities, yet fused at the lower thorax and pelvis, with a shared liver and gastrointestinal tract and a tri-podal lower-limb configuration. Following multidisciplinary consultation, the